A new species of Leptobrachella Smith 1925 (Anura: Megophryidae) from Southern Guangxi, China - Chen, Weicai; Peng, Wanxiao; Pan, Weihu; Liao, Nanyan; Liu, Youjun; Huang, Yong (Zootaxa, 2021)
We described a new species of the genus Leptobrachella from Southern Guangxi, China, based on morphological characteristics, molecular analyses and bioacoustics. This new species, Leptobrachella shiwandashanensis sp. nov., occurs in sympatry with Leptobrachella shangsiensis. However, phylogenetic analyses based on the mitochondrial 16S gene fragment revealed that the new species was clustered in a monophyletic group and a considerable genetic divergence existed between the new species and L. shangsiensis (p-distance: 7.9%) as well as its congeners (minimum p-distance: 7.0%). The new species also differed from its congeners by a combination of the following characteristics: (1) small size (SVL 26.8–29.7 mm in males; 33.7–35.9 mm in females); (2) pale brown dorsal surfaces, with a brown inverse-triangle-shaped marking between the eyes; (3) creamy white ventral surface with brown spots on the lateral margin, with a near immaculate creamy white throat and chest; (4) without webbing and lateral fringes on toes; (5) flanks with irregular black spots; (6) tibia-tarsal articulation reaching the posterior of the eye in males but reaching the shoulder in females; (7) heels that do not meet when the thighs are appressed at right angles to the body; (8) bicolored iris, with the upper half brownish-red, fading to silver in the lower half; and (9) a call consisting of a single note and a dominant frequency of 5.3–5.7 kHz (recorded at 23°C).